Periodic Solutions for Gause-Type Ratio-Dependent Predator-Prey Systems with Delays on Time Scales - Xiaoquan Ding; Hongyuan Liu; Fengye Wang (Discrete Dynamics in Nature and Society)
This paper is devoted to periodic Gause-type ratio-dependent predator-prey systems with monotonic or nonmonotonic numerical responses on time scales. By using a continuation theorem based on coincidence degree theory, we establish easily verifiable criteria for the existence of periodic solutions. In particular, our results improve and generalize some known ones.